Law Enforcement For Clothes Smuggling Formallyillegal - Ridwan Lubis, Muhammad (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
The crime of smuggling is very common in Indonesia, it's just that in imposing criminal sanctions, its implementation only focuses on imprisonment, because the concept of "state compensation" is not explicitly regulated in the sentence structure of the Customs Law, namely every time a government smuggling crime occurs, it is always dangerous. . This research uses a descriptive method through a normative approach (legal research), namely a problematic approach that is carried out through a study of various legal aspects related to applicable laws and regulations. The results of the study show that Indonesia's legal regulations regarding smuggling are Law no. 17 of 2006. A form of illegal used clothing crime related to customs in the territory of the Republic of Indonesia occurs on the coast outside the port area, using both traditional and modern equipment and usually without official documents. Trafficking in persons or legal entities is punishable by cumulative criminal penalties, namely imprisonment and fines. This sanction appears in Articles 102A and 102B of the Customs Law No 17 of 2006. Keywords: Law Enforcement, Smuggling, Used Clothing.